Thermal history and behavioural plasticity shape reef fish tolerance to marine heatwaves - Angus Mitchell; Sean D. Connell; Ben P. Harvey; Sylvain Agostini; Jeffrey Jolly; Guinther Mitushasi; Timothy Ravasi; David J. Booth; Ivan Nagelkerken (Coral Reefs, 2026)
Marine heatwaves are becoming more frequent and intense, driving mass fish mortalities and reshaping marine ecosystems, yet the capacity of fishes to tolerate heatwaves remains unclear. We quantified physiological condition and behavioural responses of juvenile warm-water ( Abudefduf vaigiensis ) and cool-water ( Microcanthus strigatus ) fishes from three natural climate analogues—an ambient temperate reef, an ocean warming analogue, and a combined warming and extreme acidification analogue—before and during the 2023 global marine heatwave, and under a + 3 °C simulated heatwave in the laboratory. In the laboratory, warm-water fish from the warm reef began the experiment in leaner condition than cool reef fish but increased their bite rates under heatwave conditions, compensating for elevated metabolic demand and maintaining body condition. Cool-water fish showed no behavioural adjustment to the heatwave, and body condition diverged by reef origin: cool reef fish lost weight across all treatments while warm- and extreme-origin fish maintained condition, suggesting tolerance was conferred by prior thermal history rather than acute behavioural responses. In the field, warm-water fish were leaner and had lower protein content during the 2023 heatwave than before it, while cool-water fish from the extreme reef had lower body condition than those from the cool reef prior to the heatwave. Our findings suggest that behavioural plasticity can facilitate warm-water fish tolerance to heatwaves at their cold leading edges, while thermal history supports heatwave tolerance in cool-water fish within their core ranges. Populations inhabiting naturally extreme climate analogues may therefore harbour pre-adapted, climate-resilient fish in a future ocean.